Classification of Individual Pain Response Trajectories Following Medically Indicated Heel Lances in Preterm Infants During Their NICU Admission. Issue 3 (March 2022) - Hundert, Amos; Woolcott, Christy; Dorling, Jon; Benoit, Britney; Campbell-Yeo, Marsha
Abstract : Objectives: Infants born preterm are exposed to repeated painful procedures during neonatal intensive care unit admission. Particularly in preterm infants, trajectories of pain response are not well understood. The aim of this study was to classify pain response trajectories over 2 minute following medically indicated heel lances in preterm infants. Materials and Methods: This study used existing clinical trial data (NCT01561547) that evaluated the efficacy of kangaroo care and sucrose for infant pain control. Pain was measured using the Premature Infant Pain Profile at 30, 60, 90, and 120 seconds following a heel lance. Group-based trajectory modeling was used to classify pain response in this 2 minute period. Results: A total of 236 infants with median gestational age of 33 weeks contributed 610 procedures. A model with 5 trajectory classes best fit the data. Three trajectories were stable over time at different levels of intensity from low-mild to low-moderate pain. One trajectory reflected a linear reduction from high-moderate to low-moderate pain. The final trajectory showed variable moderate-high pain. At all times points, 3 classes were at least 1-point different from the overall sample mean pain score. Only 21 (9%) infants maintained the same class for all 3 procedures. Discussion: In this sample of preterm infants receiving pain relief, most pain trajectories reflected mild to low-moderate pain that was stable over 2 minute after heel lance initiation. Trajectories were not consistent over multiple procedures within infants, and an overall mean pain score for the sample may misrepresent subgroups of pain response.